Unmanipulated haploidentical peripheral blood stem cell transplantation for patients with Philadelphia-negative acute lymphoblastic leukaemia in first complete remission. Issue 1 (2nd January 2020) - Wang, Feiyan; Liu, Tong; Wang, Li; Gu, Zhenyang; Yang, Nan; Luo, Lan; Zhu, Chengying; Li, Meng; Liu, Daihong; Gao, Chunji
Abstract: Haploidentical peripheral blood stem cell transplantation (Haplo-PBSCT) is a promising treatment option for patients with Ph-negative acute lymphoblastic leukemia (ALL). In this study, we retrospectively analyzed data from Ph-negative ALL patients who underwent haplo-PBSCT during their first complete remission (CR1), and compared the long-term outcomes between the standard-risk and high-risk patients. The 3-year probability of relapse was 7.6% and 16.7% for the standard- and high-risk group ( p  = .274). The 3-year probability of disease-free survival (DFS) and overall survival (OS) for the standard-risk versus high-risk groups were 84.6% versus 50% ( p  = .0063) and 92.3% versus 61.1% ( p  = .046), respectively. Univariate analysis showed that a diagnosis of high risk with fusion/mutation genes were associated with worse outcomes, which was confirmed by multivariate analysis ( p  = .016). In summary, haplo-PBSCT may be a promising alternative for patients with Ph-negative ALL in CR1, although the fusion/mutation genes in high-risk patients may relatively impair the long-term efficacy compared with standard-risk patients.